Root surface treatment with vitamin C in tooth replantation: microscopic study in rats - Barioni, Sônia Regina Panzarini [UNESP]; Poi, Wilson Roberto [UNESP]; Pedrini, Denise [UNESP]; Sonoda, Celso Koogi [UNESP]; Brandini, Daniela Atili [UNESP]; Luvizuto, E. R. (My University, 2008)
AIM: Late tooth replantation is a worthy procedure, especially in growing patients, being the best option for tooth avulsion. This study evaluated the effects of root surface treatment with 2% acidulated phosphate sodium fluoride and effervescent vitamin C (Redoxon) in late replantation. METHODS: Twenty rat teeth (Rattus norvegicus, albinus, Wistar) were extracted and left on a table for 6 h. Then, the dental papilla and enamel organ were sectioned and the pulp was removed through the apex. After removal of the periodontal ligament with a blade, the animals were divided into 2 groups: Group I teeth were immersed in 2% acidulated phosphate sodium fluoride solution for 10 min and obturated with Ca(OH)(2) paste. Group II teeth were immersed in effervescent vitamin C solution (Redoxon 2 g) for 10 min and obturated as for Group I. After these procedures, teeth were replanted and animals were killed after 60 days. RESULTS: The study revealed a larger amount of replacement resorption in Group I and larger amount of ankylosis in Group II, with statistically significant difference and absence of inflammatory resorption. CONCLUSION: The substances used for root surface treatment were unable to prevent replacement resorption and ankylosis, which are expected when the periodontal ligament has been lost.
Keywords: ascorbic acid; animal; comparative study; drug effect; endodontics; methodology; rat; tooth root; ultrastructure; Wistar rat; Animals; Ascorbic Acid; Rats; Rats, Wistar; Tooth Replantation; Tooth Root